Penundaan Perkawinan Bagi Wanita Karir dalam Perspektif Yusuf al-Qaradhawi - Angriati, Ririn; Aisyah, Siti; Sastrawati, Nila; Nurtita, Nurtita (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Career for some women is proof of the achievements of their abilities so they often postpone marriage to focus more on their careers. This study aims to determine the factors behind the postponement of marriage for women as well as M. Yusuf Al-Qardawi views on postponing marriage for career women. This type of research is qualitative research with a Syar'i Normative approach. The data sources used in this study are primary data including the Qur'an, Hadith and secondary data in the form of books, articles, journals, and tertiary data in the form of dictionaries and encyclopedias related to the postponement of marriage for career women. Data obtained both primary and secondary are then collected, and analyzed in depth. The results of this study show that the reason for women to have a career is to fulfill the wishes of their parents, social status in society, do not want to be bound (want to be free). Other reasons women postpone marriage are job requirements, culture and traditions of society, and sometimes they have not found a suitable partner. Yusuf Qardhawy argued about career women that women who have careers outside the home are allowed in Islam under certain conditions, but he also explained that the main duty of women is to be um wa robbatu al-bayyit. Women according to Yusuf Qardawi have the main obligation to their husbands and educate their children, and with a woman postponing marriage because of career of course her main obligations in the household will be neglected. Therefore, Yusuf Qaradawi's fatwas indicate that if a Muslim woman postpones marriage because of her career without justified reasons, Sharia is not in line with Islamic law.